Improving robustness of Texas instrument's simpliciti protocol on EZ430-RF2500 - Umayi Kalyanaramudu Harishkumar (2009)
Wireless communications has become one of the fastest growing segments of the communications industry. It has captured the attention of the media and the imagination of the public. One of its applications, Wireless local area networks have currently supplemented or replaced wired networks in many homes, businesses, and campuses. Many new applications – including wireless sensor networks, automated highways and factories, smart homes and appliances, and remote telemedicine – are emerging from research ideas to concrete systems. The explosive growth of wireless systems coupled with the proliferation of laptop and palmtop computers suggests a bright future for wireless networks, both as stand-alone systems and as part of the larger networking infrastructure. However, many technical challenges remain in designing robust wireless networks that deliver the performance necessary to support emerging applications. In this project the spread spectrum techniques used to enable wireless services to coexist in the industrial scientific and medical (ISM) band are studied. A suitable technique for SimpliciTI protocol (Texas Instruments low power RF network protocol) is proposed to improve its robustness in the unregulated ISM band. The development of frequency agility in SimpliciTI is provided in a step by step approach using the eZ430 - RF2500 developmental tool. A frequency jammer is developed to simulate RF interference in the specified band. A wireless sensor network is setup to test the developed frequency agility feature of SimpliciTI. A graphical User Interface is developed to demonstrate the working of the frequency agile system.